2022
DOI: 10.3390/socsci11090383
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to Governmental Income Supports for Sex Workers during COVID-19: Results of a Community-Based Cohort in Metro Vancouver

Abstract: The COVID-19 pandemic has brought into stark focus the economic inequities faced by precarious, criminalized and racialized workers. Sex workers have been historically excluded from structural supports due to criminalization and occupational stigma. Given emerging concerns regarding sex workers’ inequitable access to COVID-19 income supports in Canada and elsewhere, our objective was to identify prevalence and correlates of accessing emergency income supports among women sex workers in Vancouver, Canada. Data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 31 publications
(65 reference statements)
0
6
0
Order By: Relevance
“…These TDRM trends are affected by environmental and economic factors, including the COVID-19 pandemic. In fact, a recent study conducted in Canada revealed that drop-in services and outreach work by commercial sex workers were reduced due to COVID-related restrictions 27 . Access to healthcare also declined significantly during the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…These TDRM trends are affected by environmental and economic factors, including the COVID-19 pandemic. In fact, a recent study conducted in Canada revealed that drop-in services and outreach work by commercial sex workers were reduced due to COVID-related restrictions 27 . Access to healthcare also declined significantly during the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…The authors draw on data gathered from an ongoing community-based study to identify the prevalence and correlates of accessing emergency income support during the first year of the COVID-19 pandemic, including the Canada Emergency Response Benefit (CERB), a one-time benefit available to Canadian residents based on their previous earnings and tax returns. Pearson et al (2022) show that sex workers in Vancouver not only lost significant income from the sale of sexual services due to shutdowns and mobility restrictions, but were far less likely than other service workers to access government income support during the first year of the COVID-19 pandemic. The outcome of these macro-level forces was greater poverty for sex workers in Vancouver's inner city, exacerbated housing precarity, and increased food insecurity.…”
Section: Overview Of Included Papersmentioning
confidence: 97%
“…The impacts of the COVID-19 pandemic have left gaps in knowledge that are not only essential to address now but also in preparation for future pandemic planning in the health system. Structural health inequities, including, access to healthcare services and community-based services (10,(12)(13)(14)(15), gender-based violence (16,17), and mental health disparities (14,18,19) have been impacted by the COVID-19 pandemic (20), yet little is known about marginalized Indigenous cisgender and transgender women and Two-Spirit Peoples access to routine healthcare services during the pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…Sex workers and women living with HIV have been affected by the COVID-19 pandemic facing loss of income and lack of access to outreach services as well as stigmatization and harassment by governments and police ( 22 , 23 ). Gendered impacts of COVID-19 include increased economic insecurity, unplanned pregnancy, lack of access to health services, domestic violence, lack of women’s voice and agency, and mental health issues ( 6 , 12 , 15 , 24 ). The impacts are particularly felt by racialized groups that are marginalized by social and structural inequities, including Indigenous women and Two-Spirit Peoples.…”
Section: Introductionmentioning
confidence: 99%